A Multi-Channel Asynchronous Neurostimulator With Artifact Suppression for Neural Code-Based Stimulations - Elyahoodayan, Sahar; Jiang, Wenxuan; Xu, Huijing; Song, Dong (Frontiers in Neuroscience, 2019)
A novel neurostimulator for generating neural code-based, precise, asynchronous electrical stimulation pulses is designed, fabricated and characterized. Through multiplexing, this system can deliver constant current biphasic pulses, with arbitrary temporal patterns and pulse parameters to 32 electrodes using one pulse generator. The design also features a stimulus artifact suppression technique that can be integrated with commercial amplifiers. Using an array of CMOS switches, electrodes are disconnected from recording amplifiers during stimulation, while the input of the recording system is shorted to ground through another CMOS switch to suppress ringing in the recording system. The timing of the switches used to block and suppress the stimulus artifact are crucial and are determined by the electrochemical properties of the electrode. This system allows stimulation and recording from the same electrodes to monitor local field potentials with short latencies from the region of stimulation for achieving feedback control of neural stimulation. In this way, timing between each pulse is controlled by inputs from an external source and stimulus magnitude is controlled by feed-back from neural response from the region of stimulation. The system was implemented with low-power and compact packaged microchips to constitute an effective, cost-efficient and miniaturized neurostimulator. The device has been first evaluated in phantom preparations and then tested in hippocampi of behaving rats. Benchtop results demonstrate the capability of the stimulator to generate arbitrary spatio-temporal pattern of stimulation pulses dictated by random number generators to control magnitude and timing between each individual biphasic pulse. In vivo results show that evoked potentials elicited by the neurostimulator can be recorded ~2ms after the termination of stimulus pulses from the same electrodes where stimulation pulses are delivered, whereas commercial amplifiers without such an artifact suppression typically result in tens to hundreds of milliseconds recovery period. This neurostimulator design is desirable in a variety of neural interface applications, particularly hippocampal memory prosthesis aiming to restore cognitive functions by reinstating neural code transmissions in the brain.